17. THE KNOWLEDGE, ATTITUDES, AND PRACTICES OF HAND, FOOT AND MOUTH DISEASE PREVENTION AMONG MOTHERS OF CHILDREN UNDER FIVE YEARS OLD AT LE VAN THINH HOSPITAL (Vietnam Journal of Community Medicine, 2024)
Objective: Determine the proportion of mothers with children under 5 years old at Le Van Thinh Hospital clinic in Thu Duc City who have the correct knowledge, positive attitudes, and correct practices on Hand, foot, and mouth disease (HFMD) prevention.Methods: A cross-sectional study was conducted on 304 mothers of children under 5 years old at Le Van Thinh Hospital in Thu Duc City from February to May 2024. Describe qualitative variables using frequencies and percentages and test the relationships by Chi-square test or Fisher test with α = 0,05, then estimate the relationships by prevalence ratio (PR) with 95% confidence interval, p-value
Keywords: Hand foot and mouth disease, knowledge, attitude, practice, mothers